Analysis of the Raccoon (Procyon lotor) and Common Raccoon Dog (Nyctereutes procyonoides) Spatiotemporal Changes Based on Hunting Bag Data in Hungary - Gergely Schally; Hanna Bijl; Bhraaz Kashyap; Mihály Márton; Szilvia Bőti; Krisztián Katona; Zsolt Biró; Miklós Heltai; Sándor Csányi (Diversity)
Sustainable wildlife management requires reliable data on population, habitat, and the interaction between them. Since 1993, Hungary has maintained the National Game Management Database, which collects data on game populations and hunting bags annually. During the last three decades, populations of medium-sized predators have remarkably increased in the country. Our study analyzed changes in hunting bag data and spatial distribution of two invasive alien species, the raccoon (Procyon lotor) and the raccoon dog (Nyctereutes procyonoides), utilizing annual game management reports from Game Management Units from 1997 to 2021. For spatial analysis, we employed a UTM grid system (10 × 10 km) covering the country. Our findings confirmed increasing trends in the hunting bag and area (number of grid cells) containing hunting bags for both species. From the first (1997–2001) to the last (2017–2021) period, the average annual hunting bag increased (raccoon: 0.40 → 11.00 ind/year; raccoon dog: 3.40 → 8.00 ind/year), and the average number of cells with hunting bags also expanded significantly (raccoon: 2.00 → 9.60 UTM cells/year; raccoon dog: 5.80 → 15.20 UTM cells/year). These trends and the size of potentially suitable habitats suggest a further spread and population increase, posing challenges for nature conservationists and wildlife managers.